Arctic National Wildlife Refuge (ANWR): Controversies for the 108th Congress - Corn, M. Lynne; Gelb, Bernard A.; Baldwin, Pamela (Library of Congress. Congressional Research Service., 2003)
This report is a brief of the controversies for the 108th Congress regarding the Arctic National Wildlife Refuge (ANWR).